Pulsed technology for manual arc welding of thin-walled structures by coated electrode - V. F. Mukhin; E. N. Eremin; Yu. O. Filippov (Омский научный вестник)
The article presents the results of work on the study of the use of a single-phase rectifier with an additional unit for obtaining pulsed modes for manual arc welding with thin-walled construction by a stick electrode. The proposed scheme of an additional block allows by selecting the parameters of the welding mode to ensure a stable quasistationary process of melting and transfer of the electrode metal. Thus, it becomes possible to weld thin-sheet structures without reducing the diameter of the coated electrode.